Establishment and evaluation of the goose embryo epithelial (GEE) cell line as a new model for propagation of avian viruses. - Wenxiu Wang (PLoS ONE, 2018)
In this study, we report the establishment and characterization of a new epithelial cell line, goose embryonated epithelial cell line (GEE), derived from embryonic goose tissue. The purified GEE cell line can efficiently grow over 65 passages in the M199 medium supplemented with 10% fetal bovine serum at 37°C. Immunofluorescence assay was used to identify purified GEE cells as epithelial cell line by detecting expression of the Keratin-18 and -19. Further characterizations demonstrated that the GEE cell line can be continuously subcultured with (i) a high capacity to replicate for over 65 passages, (ii) a spontaneous epithelial-like morphology, (iii) constant chromosomal features and (iv) without an evidence of converting to tumorigenic cells either in vitro or in vivo study. Moreover, the GEE cell line can be effectively transfected with plasmids expressing reporter genes of different avian viruses, such as VP3, VP1 and F of goose parvo virus (GPV), duck hepatitis virus (DHV), and Newcastle disease virus (NDV), respectively. Finally, the established GEE cell line was evaluated for avian viruses infection susceptibility. Our results showed that the tested GPV, DHAV and NDV were capable to replicate in the new cell line with titers a comparatively higher to the ones detected in the traditional culture system. Accordingly, our established GEE cell line is apparently a suitable in vitro model for transgenic, and infection manipulation studies.